Water Sample Collection Methods for 222Rn Analysis by Scuba Diving: Insights on Groundwater Flushing of Anchialine Cave Systems of the Yucatan Peninsula - M. Bayani Cardenas; Ivo Chiarino; Josiah M. Sananda; William D. Nguyen; Daniella M. Rempe (Water Resources Research)
Abstract Radon (222Rn) is a widely used tracer in groundwater and surface water studies. In some applications of radon, samples need to be collected from deep submerged areas or discharge points such as caves or springs, locations typically accessed by scuba diving. However, there are no established sampling methods for collecting water by scuba diving for Rn analysis. We assessed four underwater sample collection methods: (a) injection into a catheter bag followed by transfer to a bottle after the dive, (b) air purging and then filling of a bottle by allowing gas to escape, (c) air purging followed by gas escape, and then overfilling of water with a syringe, and (d) collection with a syringe followed by transfer to a bottle. The samples were collected from the anchialine caves of the Yucatan Peninsula which are the longest underwater cave systems. The samples were analyzed using the same Rn‐in‐air analyzer and protocols. Statistical comparison of sampling at the same location with different methods showed no significant differences in Rn activity. No collection method is superior in terms of measurement quality; operational simplicity is thus preferred. Statistically significant differences in activity were observed between fresh and saline samples from the same cave, with higher activities in the fresh samples, regardless of sampling method. The saline groundwater therefore has a lower residence time, suggesting vigorous landwards flow. Our assessment shows that in situ sampling of discrete water samples for Rn tracing by divers is a useful and powerful approach allowing the study of otherwise impossible sites.